Students’s Attitudes Toward the Use of CANVAS in the EFL Virtual Learning Environment - Santiana, Santiana; Margana, Margana; Pancoro Setyo Putro, Nur Hidayanto; Widodo, Pratomo (Universitas Negeri Makassar, 2024)
This study examines students’ attitudes toward the Learning Management System (hereafter LMS) CANVAS in the Virtual Learning Environment (henceforth VLE). This study used mixed methods in nature, which used a survey to collect data on the attitudes of 118 EFL students who enrolled in the Technology Enhanced Language Learning (hereafter TELL) course. Researchers gathered data through a questionnaire and semi-structured interviews to assess students’ attitudes using the Technology Acceptance Model (TAM). The survey results were analyzed using descriptive statistics to investigate the quantitative data, while thematic analysis was used to study the qualitative data obtained from interviews. The survey results were analyzed using descriptive statistics to investigate the quantitative data, while thematic analysis was used to study the qualitative data obtained from interviews. Based on the research findings, the TAM framework identifies two main categories: Perceived Usefulness and Perceived Ease of Use. The Perceive Usefulness category comprises four categories: CANVAS Engagement Time, CANVAS Enhances Interaction, Learning Efficacy, and Effective Communication, CANVAS Enhances Language Learning, and CANVAS Boosting Students’ Confidence and Motivation in a Fun Way. In addition, the Perceive Ease of Use category comprises three categories: CANVAS Usability in Mobile Learning Environments, CANVAS User-Friendly Design, and CANVAS Seamless Navigation and Accessibility.